A digital-twin visualized architecture for Flexible Manufacturing System. (July 2021) - Fan, Yepeng; Yang, Jianzhong; Chen, Jihong; Hu, Pengcheng; Wang, Xiaoyu; Xu, Jianchun; Zhou, Bin
Graphical abstract: Highlights: We present a generic architecture and implementation method for a flexible manufacturing system digital-twin visualization. The concept of Geometric-Historical-Object-Snapshot-Topology (GHOST) modeling for FMS life cycle DT is proposed. GHOST service prototype and multi-platform generic visual app software (Visual Field) prototype are developed. Abstract: The new generation of industrial 4.0 intelligent manufacturing system consists of Human-Cyber-Physical System (HCPS), integrating human with cyber and physical systems. In manufacturing, a digital-twin visualization architecture is to solve the human-machine interaction problem that concerns digital-twin modeling on the Cyber-Physical (C-P) side and on the Human-Cyber side. Although there are many related research and applications, there lacks attention in terms of full life cycle functional services and lightweight architecture. This paper presents a general architecture of digital-twin visualization for flexible manufacturing systems (FMS). How the digital-twin C-P modeling of multi-source heterogeneous information can be described is investigated and how the 3D visualized human-machine interaction with digital-twin scenario information is explored in the proposed architecture. Besides, the visualization method of high-value information, relating to the life cycle planning, design, debugging and service stages, is studied and discussed thoroughly. Also, a digital-twin modeling concept of "Geometric information (G)-Historical samples (H)-Object attribute (O)-Snapshot collection (S)-Topology constraint (T)" (GHOST) is proposed, and methods for developing virtual digital-twin scenes architecture are presented. Based on the proposed modeling concept of GHOST for digital-twin, prototypes have been developed for the general platform of digital-twin RESTful services and the cross-platform general visual mock-up software. Experimental results show that this method is effective in the FMS lifecycle in various aspects.